Design Of Internal Control Systems, Accounting Records, And Financial Reporting Of Cv Multi Metalindo - Sukiantono Tang; Mita Permata Sari (Universitas Internasional Batam, 2023)
This activity is carried out to apply the accounting knowledge learned during college into daily business. In addition, this activity also aims to help micro business actors make accurate and correct books and financial reports to reflect the economic situation of the business. The object of this activity is CV Multi Metalindo, a company that has been operating for a long time but still uses semi-manual records in its books, and does not yet have good financial reports. This condition is known by visiting the place of business and also by interviewing. This activity resulted in accounting students designed in the Microsoft Access program so that entrepreneurs can easily make records and the system can automatically generate financial reports. This system can also improve business flow to more efficient and effective business operations.